Species of Wadicosa (Araneae, Lycosidae): a new species from the southeastern Arabian Peninsula - Kronestedt, Torbjörn; Feulner, Gary R.; Roobas, Binish (Zootaxa, 2024)
Wadicosa arabica sp. nov. is described from material of both sexes collected in Oman and the United Arab Emirates. The species belongs to the W. fidelis group and differs from its congroupers, inter alia, by the shape of the tegular apophysis and the embolus in the male. The occurrence of W. arabica sp. nov. is restricted to the gravel, pebble and cobble beds of ephemeral and intermittent streams (wadis) in the mountains of the eastern United Arab Emirates and northern Oman (the Hajar Mountains sensu lato). There it is often common and conspicuous alongside areas of surface waters. Notes on its courtship behaviour are given.